Exploring the mitigating potential of anthocyanin Malvidin in a mouse model of bleomycin-induced pulmonary fibrosis by inhibiting NLRP3 inflammasome activation and oxidative stress - Dingzi Zhou; Lin Cai; Jie Xu; Daigang Fu; Ling Yan; Linshen Xie (Journal of Inflammation)
Abstract Background Malvidin (MV), an essential anthocyanin, has antioxidant and anti-inflammatory effects that may help treat pulmonary fibrosis (PF), a progressive and occasionally fatal condition characterized by severe lung scarring, oxidative stress, and inflammation. Objective This study aims to evaluate the therapeutic potential of MV in PF by assessing its effects on inflammation, oxidative stress, and fibrotic markers through in vitro and in vivo models. Methods and materials The compound was evaluated by molecular docking. BEAS-2B and RLE-6TN cells were treated with 200 µg/mL BLM to induce inflammation, followed by MV treatment. Cell viability, ROS levels, and wound healing were analyzed. In vivo, BLM-induced mice were evaluated to assess fibrotic and antioxidant biomarkers. Results MV interacted with NLRP3 with a binding energy of -7 kcal/mol. MV increased cell viability in BLM-induced cells, reducing ROS and oxidative stress. Wound healing was enhanced in MV-treated groups. A decrease in HYP proteins confirms MV’s antifibrotic effects. In the mice model, MV reduced TXNIP, MDA, and MPO while increasing CAT, GSH, and SOD, confirming its antioxidant capacity. Conclusion MV alleviated PF in the BLM-induced model via the NLRP3 inflammasome pathway, demonstrating its potential as an antifibrotic and antioxidant agent.